Prevalence of tuberculosis, hepatitis C virus, and HIV in homeless people: a systematic review and meta-analysis. - Beijer, U; Wolf, A; Fazel, S (2012)
BACKGROUND: 100 million people worldwide are homeless; rates of mortality and morbidity are high in this population. The contribution of infectious diseases to these adverse outcomes is uncertain. Accurate estimates of prevalence data are important for public policy and planning and development of clinical services tailored to homeless people. We aimed to establish the prevalence of tuberculosis, hepatitis C virus, and HIV in homeless people. METHODS: We searched PubMed, Embase, and Cumulative Index to Nursing and Allied Health Literature for studies of the prevalence of tuberculosis, hepatitis C virus, and HIV in homeless populations. We also searched bibliographic indices, scanned reference lists, and corresponded with authors. We explored potential sources of heterogeneity in the estimates by metaregression analysis and calculated prevalence ratios to compare prevalence estimates for homeless people with those for the general population. FINDINGS: We identified 43 eligible surveys with a total population of 63,812 (59 736 homeless individuals when duplication due to overlapping samples was accounted for). Prevalences ranged from 0·2% to 7·7% for tuberculosis, 3·9% to 36·2% for hepatitis C virus infection, and 0·3% to 21·1% for HIV infection. We noted substantial heterogeneity in prevalence estimates for tuberculosis, hepatitis C virus infection, and HIV infection (all Cochran's χ(2) significant at p<0·0001; I(2)=83%, 95% CI 76-89; 95%, 94-96; and 94%, 93-95; respectively). Prevalence ratios ranged from 34 to 452 for tuberculosis, 4 to 70 for hepatitis C virus infection, and 1 to 77 for HIV infection. Tuberculosis prevalence was higher in studies in which diagnosis was by chest radiography than in those which used other diagnostic methods and in countries with a higher general population prevalence than in those with a lower general prevalence. Prevalence of HIV infection was lower in newer studies than in older ones and was higher in the USA than in the rest of the world. INTERPRETATION: Heterogeneity in prevalence estimates for tuberculosis, hepatitis C virus, and HIV suggests the need for local surveys to inform development of health services for homeless people. The role of targeted and population-based measures in the reduction of risks of infectious diseases, premature mortality, and other adverse outcomes needs further examination. Guidelines for screening and treatment of infectious diseases in homeless people might need to be reviewed. FUNDING: The Wellcome Trust.